2006
DOI: 10.1634/stemcells.2006-0020
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor-1 Potentiates Hematopoietic Progenitor Cell Mobilization Induced by Granulocyte Colony-Stimulating Factor in Mice and Nonhuman Primates

Abstract: The complex hematopoietic effects of placental growth factor (PlGF) prompted us to test in mice and nonhuman primates the mobilization of peripheral blood progenitor cells (PBPCs) elicited by recombinant mouse PlGF-2 (rmPlGF-2) and recombinant human PlGF-1 (rhPlGF-1). PBPC mobilization was evaluated by assaying colonyforming cells (CFCs), high-proliferative potential-CFCs (HPP-CFCs), and long-term culture-initiating cells (LTCICs). In mice, both rmPlGF-2 and rhPlGF-1 used as single agents failed to mobilize PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…32,33 Furthermore, PlGF-2 is able to contribute to the mobilization of HSCs and hematopoietic progenitor cells from the bone marrow when combined with prolonged G-CSF administration, although PlGF does not induce mobilization when administered in isolation. 19,34 Notably, under conditions of steady-state hematopoiesis, inhibition of VEGFR1 activation does not result in a profound impairment of hematopoiesis in vivo or hematopoietic progenitor cell colony formation in vitro. 32,33 Similarly, here we show that inhibition of VEGF-A 165 with a VEGFR1 blocking Ab did not reduce circulating platelet numbers below the vehicle control baseline (presumably steady-state thrombopoiesis).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Furthermore, PlGF-2 is able to contribute to the mobilization of HSCs and hematopoietic progenitor cells from the bone marrow when combined with prolonged G-CSF administration, although PlGF does not induce mobilization when administered in isolation. 19,34 Notably, under conditions of steady-state hematopoiesis, inhibition of VEGFR1 activation does not result in a profound impairment of hematopoiesis in vivo or hematopoietic progenitor cell colony formation in vitro. 32,33 Similarly, here we show that inhibition of VEGF-A 165 with a VEGFR1 blocking Ab did not reduce circulating platelet numbers below the vehicle control baseline (presumably steady-state thrombopoiesis).…”
Section: Discussionmentioning
confidence: 99%
“…PlGF reconstitutes hematopoiesis through stimulation of stem cell differentiation and mobilization (Hattori et al 2002) PlGF recruits angiogenic BM progenitors and macrophages to neovessels (Lyden et al 2001;Luttun et al 2002;Pipp et al 2003;Kaplan et al 2005;Li et al 2006;Carlo-Stella et al 2007) Viral PlGF gene delivery induces PAI1 plasma levels via mechansms involving HIF1a and miRNA regulation, and promotes a prothrombotic phenotype (Patel et al , 2011 Overexpression of PlGF in erythroid cells to mimic sickle cell PlGF levels promotes pulmonary hypertension in mice Knockout or aPlGF impairs recruitment of BM progenitors and macrophages to neovessels (Carmeliet et al 2001;Fischer et al 2007) Knockout reduces PAI1 plasma levels in sickle cell disease (Patel et al , 2011) Knockout or aPlGF increases morbidity and mortality in sepsis (Yano et al 2008) Nervous system Intramuscular PlGF gene delivery restores diabetic sensory neuropathy (Murakami et al 2011) Myocardial ischemia is a major cause of morbidity and mortality. After acute myocardial infarction (AMI), the viable cardiac tissue in the remote area and border zone undergoes hypertrophy in an effort to compensate for the ischemic muscle damage; if not supported by angiogenesis, this hypertrophy can lead to maladaptive decompensation (Shiojima et al 2005).…”
Section: Plgf a Disease-modifying Candidatementioning
confidence: 99%
“…PlGF promotes the recruitment and differentiation of bone marrow progenitors and regulates hematopoietic reconstitution after myelosuppression (Hattori et al 2002;Luttun et al 2002;Carlo-Stella et al 2007;Loges et al 2009). PlGF is released by erythroid cells and plasma PlGF is elevated in patients with sickle cell disease (SCD), correlating with hemolysis (Patel et al 2008;Brittain et al 2010).…”
Section: Hematological Homeostasis and Malignanciesmentioning
confidence: 99%
“…Using two different animal models (i.e., BALB/c mice and rhesus monkeys) that are susceptible to stimulation of mobilized peripheral blood progenitor cells, Carlo-Stella et al [29] demonstrated that human PlGF acted synergically with human granulocyte colony-stimulating factor (GM-CSF), enhancing the expression and the absolute numbers of a broad spectrum of circulating hematopoietic precursors.…”
Section: Plgf and Hematopoietic Progenitor Cells Mobilizationmentioning
confidence: 99%